(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Hydrogenases (Hyds) are microbial enzymes that reversibly catalyze the oxidation of molecular hydrogen (H₂), playing a critical role in biohydrogen metabolism [1-3]. These include oxygen-resistant biological [NiFe]-hydrogenases, which have attracted great interest for their application in hydrogen fuel cell (H₂-FC) technologies. The results provide insight into the potential of bioelectrochemical-based systems for sustainable energy production. The bioelectrocatalytic efficiency of E. coli bacteria immobilized on the electrode surface in a volume of 3 μl (1.5 mg cell dry weight) was studied under the conditions of 0.2% glucose fermentation in peptone medium at pH-7.5 [4]. In this study, the electrochemical measurements were performed using a two-electrode system equipped with a computer potentiostat, specifically a hydrogen fuel cell voltammetry (HFCV). The wild-type E. coli BW25113, the septuple (BW25113hyaB hybC hycA fdoG ldhA frdC aceE) the F0F1-ATPase-defective, and the Hyd defective hyaB, hybC, hycE, hyfG mutant strains were used in the experiments. Maximal catalytic activity was observed in the hyaB and hyfG mutants, being stimulated ∼2-fold and ∼1.6-fold compared to the wild type, reaching values of ∼1.26 ± 0.02 V and ∼0.98 ± 0.02 V, respectively. The effect of the 10 mM N,N′-dicyclohexylcarbodiimide (DCCD), the F0F1-ATPase inhibitor, on the catalytic activity of Hyd enzymes was observed. It was shown that for all strains, the reading of the voltammeter decreased 1.5 times, reaching the readings recorded by the F0F1-ATPase-defective strain. Interestingly, in the case of the the septuple mutant strain, DCCD recorded a stimulating rather than a suppressive effect. The results obtained indicate the great potential of bacteria as anodic biocatalysts and demonstrate the need for further studies.